2017
DOI: 10.1093/icb/icx029
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the “Lazy” Ants? The Function of Inactivity in Social Insects and a Possible Role of Constraint: Inactive Ants Are Corpulent and May Be Young and/or Selfish

Abstract: Social insect colonies are commonly thought of as highly organized and efficient complex systems, yet high levels of worker inactivity are common. Although consistently inactive workers have been documented across many species, very little is known about the potential function or costs associated with this behavior. Here we ask what distinguishes these "lazy" individuals from their nestmates. We obtained a large set of behavioral and morphological data about individuals, and tested for consistency with the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 121 publications
(195 reference statements)
3
36
0
Order By: Relevance
“…workers that participate in the decision-making process underlying the colony emigration only passively when carried by a primary or carrier ant towards a candidate nest. Passive ants likely correspond to the lazy ants described in the genus Temnothorax in studies of task allocation (Charbonneau and Dornhaus 2015;Charbonneau et al 2017). We also found a small proportion of workers, 3-12% of the colony, that do not fit any of the previous behavioral castes.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…workers that participate in the decision-making process underlying the colony emigration only passively when carried by a primary or carrier ant towards a candidate nest. Passive ants likely correspond to the lazy ants described in the genus Temnothorax in studies of task allocation (Charbonneau and Dornhaus 2015;Charbonneau et al 2017). We also found a small proportion of workers, 3-12% of the colony, that do not fit any of the previous behavioral castes.…”
Section: Discussionsupporting
confidence: 50%
“…Primary, carrier, passive, and fussy ants provide different contributions to the collective decisionmaking process undergoing a colony emigration that can be regarded as dividing the labor of gathering, spreading, and processing the information necessary to achieve a collective decision. While the behavior of workers (and therefore their membership in a particular behavioral caste) is stable over the course of the 5 colony emigrations we performed, we know that individual workers change the tasks they perform over time as a function of their developmental age (Tschinkel 1987;Seid and Traniello 2006;Tschinkel 2011;Kwapich andTschinkel 2013, 2016;Charbonneau et al 2017). Although the proportion of workers engaging in tandem running (i.e., primary ants) seems relatively stable (Richardson et al 2018;Pratt et al 2005Pratt et al , 2002, it remains to be shown that this is still true for each behavioral caste we identified.…”
Section: Discussionmentioning
confidence: 99%
“…Second, inactive majors may function as a "reserve" force. An empirical study on monomorphic ants demonstrated that inactive workers form a "reserve" force that becomes active when needed (Charbonneau et al, 2017). As entrance plugging is a vital task that significantly increases nest survival in C. nipponicus (Hasegawa, 1992), inactive majors may serve as "reserve" pluggers (backup) in case of the loss of the current "active" pluggers (Powell, 2016).…”
Section: Role Of "Inactive" Majorsmentioning
confidence: 99%
“…We wanted to track nurses for at least ten days because this time scale includes the entire amount of time that M. pharaonis workers tend to perform nursing behavior [14]. To track nurses over time, we anesthetized individuals with carbon dioxide and marked heads and abdomens of workers with a dot of paint using Sharpie extra-fine point, oil-based paint pens [6,22,48]. In each of five colonies, we uniquely painted 63 focal individuals with paint dots on their heads and abdomens using combinations of eight colors.…”
Section: (C) Long-term Observationsmentioning
confidence: 99%
“…Worker variation in behavioral specialization can also occur independently of age and morphology [15,16]. This interindividual variability can be the result of genetic diversity among workers [17], environmental differences during early development [18,19], variation in adult nutritional state [20][21][22], prior experience [23], and the social environment [24].…”
Section: Introductionmentioning
confidence: 99%